A New Limnonectes (Anura: Dicroglossidae) from Southern Thailand - Siriporn Yodthong; Attapol Rujirawan; Bryan L. Stuart; Anchalee Aowphol (Animals, 2021)
A new species in the dicroglossid frog genus Limnonectes is described from Ko Pha-ngan, Ko Samui, and Ko Lanta Yai Islands in southern Thailand. Males of Limnonectes pseudodoriae sp. nov. lack a caruncle on top of the head and very closely resemble L. doriae (Boulenger, 1887) from Myanmar and western and southern Thailand. However, the new species is distinguished from L. doriae and its congeners using an integrative taxonomic approach of morphology, mitochondrial DNA, and bioacoustics. Limnonectes pseudodoriae sp. nov. differs from L. doriae and its congeners by having a unique combination of morphological characters, including body size; skin texture of the interorbital region, dorsum, and shank; toe webbing; relative size of the inner metatarsal tubercle; and coloration of the tympanum, venter, and ova. The advertisement call of the new species is also readily differentiated from that of L. doriae in temporal parameters. Limnonectes pseudodoriae sp. nov. is highly divergent in mitochondrial DNA from L. doriae and its congeners, but its phylogenetic position within the genus is not resolved. The natural history of the new species is presented, and the geographic range of L. doriae in Thailand is clarified.